Anti-atherosclerosis potential activity from Alphitobius diaperinus: a molecular docking study on NLRP3 receptor - Hasibuan, Firdaus; Aritonang, Erfan Andrianto (Politeknik Negeri Jember, 2025)
This study aimed to analyze the potential activity anti-atherosclerosis of Alphitobius diaperinus larvae using molecular docking. The target receptor used was NLRP3, with β-sitosterol and campesterol as the test ligands, and simvastatin as the control ligand. The results showed that the binding affinity energies of β-sitosterol and campesterol were more negative than simvastatin, with values of -9.3, -9.3, and -8.6 kcal/mol, respectively. The inhibition constants of β-sitosterol and campesterol were lower than that of simvastatin, with values of 0.213, 0.213, and 0.494 μM, respectively. The percentage of binding site similarity with the native ligand for β-sitosterol and campesterol was 60%, while simvastatin showed 0%. Molecular probability analysis using Lipinski's rules revealed that simvastatin met all five criteria, whereas β-sitosterol and campesterol met four criteria. The LD50 analysis indicated that simvastatin fell under category III, while β-sitosterol and campesterol were in category I. All three molecules β-sitosterol, campesterol, and simvastatin were found to be non-carcinogenic. The conclusion of this study was β-sitosterol and campesterol from A. diaperinus larvae have potential as anti-atherosclerosis candidates.